Evaluation Of Tin In Amang From Rahman Hydraulic Tin Sdn. Bhd. - Ameer, Nur Dinie (Universiti Sains Malaysia, 2018)
The purpose of this research is to characterize amang from Rahman Hydraulic Tin Sdn. Bhd. and preconcentrate tin in amang. There were two different places of samples available in this research several tests were implemented in this research such as moisture content test, Loss of Ignition (LOI) test, Particle Size Distribution (PSD) analysis, X-Ray Fluorescent (XRF) analysis, X-Ray Diffraction (XRD) analysis, Scanning Electron Microscopy (SEM) analysis, Optical Microscopy, determination of density and a simple ‘floatation’ concept process. From this research, quartz (SiO2), pyrite (FeS2), arsenopyrite (AsFeS), sulphur trioxide (SO3) were found to be the highest content among the other mineral in RHT Amang. Referred to the images of SEM, cassiterite were found on interlock with other mineral. The largest quantity of mass of the amang in range size 75-125 µm. Based on LOI test, both samples can be considered to have quite high value of LOI which proved that RHT Amang have high volatile substances such as sulphide mineral. Since the RHT Amang is fine for further process to extract tin in amang, might best to use floatation method.